EFEKTIVITAS PENGGUNAAN ANTIBIOTIKA CEFEPIME DIBANDINGKAN DENGAN CEFTRIAXONE PADA PASIEN FIBRILE NEUTROPENIA ACUTE MYLOID LEUKIMIA (AML) DI RSUP Dr. KARIADI SEMARANG - Muhammad Fathurrahman; Dyah A.Perwitasari; Bayu Prio Septiantoro; Putri Ayu Lestari (Bajang Institute, 2025)
Leukemia or blood cancer is a diverse neoplastic disease, characterized by abnormal production (malignant transformation) of blood forming cells in the bone marrow and lymphoid tissue. Treatment of leukemia patients using chemotherapy. One of the side effects is Fibrile Neutropenia. Handling efforts have been done but have not provided maximum effect. Therefore there is a need for other treatments such as the use of antibiotic monotherapy. The purpose of this study was to determine the pattern of antibiotic administration in patients with AML who were diagnosed with neutropenia after induction chemotherapy and to know the effectiveness of cefepim antibiotics and ceftriaxone for treating neutropenic fever in AML after induction chemotherapy at RSUP Dr. Kariadi Semarang.The research method used was a retrospective cohort study based on primary data from the patient's medical record. The study was conducted by tracing data on medical records of patients at RSUP Dr. Kariadi Semarang analysis can be carried out using independent t test.The results showed 47 fibrile neutropenia patients who met the inclusion criteria. The mortality rate of cefepime antibiotics was 17.39% and ceftriaxone was 16.67%. The life expectancy of cefepime antibiotics was 82.61% and ceftriaxone was 83.33%. The antibiotic culture showed that 16.67% was resistant to cefepime antibiotic and 43.48% was resistant to ceftriaxone. 56.52% are still sensitive to Ceftriaxon and 83.33% are still sensitive to Cefepime. The ANC level has a significant difference (P-value of < 0.05), while in the analysis of decreased body temperature There is also a significant difference (P-value of < 0.05).From these results it can be concluded that cefepime antibiotics are more effective than ceftriaxone antibiotics in patients with AML fibrile neutripenia.